Application of project based learning learning models to improve student learning results techniques of manufacturing images of vocational school students - Donny Yudika Prasetya; Suparmin Suparmin; Arif Bintoro Johan (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of the study was to determine the increase in learning outcomes of manufacturing engineering subjects in class XI Vocational School 3 MuhammadiyahÂ Yogyakarta. This research is Classroom Action Research. Subjects were students of class XI TP 1 of Vocational School 3 MuhammadiyahÂ Yogyakarta, amounting to 21 students, while the object of the research was the activity and learning outcomes of manufacturing drawing engineering subjects. The technique of collecting data uses observation, tests and documentation. The instruments used were learning outcomes tests and observation sheets. The data analysis technique uses quantitative analysis to determine learning outcomes.The results of this study indicate that the Project Based Learning Model can improve student learning outcomes in the lathe machining engineering subjects of class XI Muhammadiyah 3 Yogyakarta Vocational School, the average value of student learning outcomes in the first cycle is 66.67% increasing to 78.81%, in the second cycle, then increased to 89.52% in the third cycle so as to reach the determined minimal completeness criteria.